Create, relate & pop @ the library services & programs for teens & tweens - Helmrich, Erin 1972-; Schneider, Elizabeth 1980- (Neal-Schuman Publishers, 2011)
Describes a framework for providing pop culture-relevant services and programs for tweens and teens; and includes descriptions of forty-seven programs.